SPUR 2021
DOI: 10.18833/spur/5/2/2
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduates Graph Interpretation and Scientific Paper Reading Shift from Novice- to Expert-like as a Result of Participation in a Summer Research Experience: A Case Study

Abstract: Research Experiences for Undergraduate (REU) programs often introduce students to scientific research and STEM career possibilities. However, the program impact on students and their research skill development is not well understood. In a case study with 10 REU students, the authors used eye-tracking and self-report data to determine student strategies for reading scientific papers and interpreting graphs at the beginning and end of the program. The strategies of REU students and science experts were then comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…We found that most RECCS mentors tended to focus their assessment of student growth on areas of research and technical skills, or critical thinking and problem-solving skills, however more than a quarter also noticed students' personal gains, such as confidence and comfort in a research environment. In a separate study, we measured the skill gains around paper and graph reading of RECCS students using eye tracking technology and showed that student skills over the course of the nine-week program became more expert-like, corroborating the self-reported data of RECCS students and their mentors who describe they gained research skills [20]. We argue that along with these gains in skills, increased confidence and the ability of students to see themselves as scientists are critical components of RECCS students' success.…”
Section: Student Growth Throughout a Summer Research Experience Has M...supporting
confidence: 60%
See 1 more Smart Citation
“…We found that most RECCS mentors tended to focus their assessment of student growth on areas of research and technical skills, or critical thinking and problem-solving skills, however more than a quarter also noticed students' personal gains, such as confidence and comfort in a research environment. In a separate study, we measured the skill gains around paper and graph reading of RECCS students using eye tracking technology and showed that student skills over the course of the nine-week program became more expert-like, corroborating the self-reported data of RECCS students and their mentors who describe they gained research skills [20]. We argue that along with these gains in skills, increased confidence and the ability of students to see themselves as scientists are critical components of RECCS students' success.…”
Section: Student Growth Throughout a Summer Research Experience Has M...supporting
confidence: 60%
“…Prior studies also described a wide range of skill and knowledge gains ranging from disciplinary content knowledge that allowed students to situate a research question in their field of study, to the development of research skills such as data collection and analysis in laboratory and field studies, e.g., [16][17][18][19]. Studies further described that students developed an overall understanding of the scientific process, including the reading of primary scientific literature; and intellectual skills such as working collaboratively, critical thinking, leadership, and scientific communication, e.g., [16][17][18][19][20]. Finally, prior studies described REU programs as formative for the development of students' identities as scientists and a sense of belonging to the scientific community [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Cohen (1990) noted that simplicity of describing data suggests the use of graphs and diagrams that may aid in presenting a program outcome. The use of figures may efficiently represent descriptive data, and is a common practice in this journal (Barney 2017;Brooks et al 2019;Garrett et al 2021;Gold, Atkins, and McNeal 2021;Kuan and Sedlacek 2022;Szecsi et al 2019). Tufte (1983) outlined the characteristics of graphical excellence, including graphs that serve the clear purpose of description, which encourage the viewer to think about substance, and encourage comparisons between different pieces of data.…”
Section: Descriptionmentioning
confidence: 99%